Plants to Polyelectrolytes: Theophylline Polymers and Their Microsphere Synthesis. Issue 8 (23rd February 2017) - Guterman, Ryan; Antonietti, Markus; Yuan, Jiayin
Abstract : Theophylline is a naturally occurring alkaloid extracted from chocolate and tea and is derivatized to synthesize a cationic polyelectrolyte by free‐radical polymerization. Dispersion polymerization of the monomer in MeOH/EtOH mixtures allows for tuning of the microsphere sizes in an easy fashion. This work represents an ongoing effort to harness natural products for polyelectrolyte synthesis. Abstract : To extend fossil oil supplies, sustainable feed stocks for the production of useful reagents and polymers should be harnessed. In this regard, chemicals derived from plants are excellent candidates. While the vast majority of plant sources used for polymer science only contain C x H y O z, alkaloids such as caffeine, nicotine, and theophylline possess nitrogen functionality that can provide new functions for bioderived polymers and their synthesis. In this context, the chemistry of theophylline, a natural product found in chocolate and tea, is exploited to create a cationic "poly(theophylline)" in a straightforward fashion for the first time. This work demonstrates how this new polymer can be synthesized and used for the creation of narrowly disperse cationic microspheres.